Dampak Penetapan Kelompok Bersenjata Sebagai Teroris Oleh Negara Lain Dalam Tinjauan Hukum Internasional - Grenaldo Milando Saleky; Lucia Charlota Octovina Tahamata; Wilshen Leatemia (Faculty of Law Pattimura University, 2022)
Introduction: Terrorism is an international crime that poses a danger to security, world peace and harms the welfare of the community, it needs to be eradicated in a planned and sustainable manner so that the human rights of the people can be protected and upheld.Purposes of the Research: This writing aims to study and discuss an armed group that can be designated as a terrorist in terms of international law and to examine and discuss the impact of the designation of an armed group as a terrorist by another country in terms of international law. Methods of the Research: The method used is a normative juridical research method using a case approach, a statutory approach and a conceptual approach.Results of the Research: The results obtained from this research are, An Armed Group can be designated as a Terrorist in terms of International Law are: The designation of an Armed Group as a terrorist is not specifically regulated in International Law. But in this case it is related to the designation of Hamas as a terrorist by several existing countries, based on the provisions of the conventions on the protection of children's rights in the Israeli and Palestinian conflicts in the 1989 Convention on the Rights of the Child (CRC), Resolution 44/25 (Convention on the Rights of the Child) Article 39 and the protections for civilians regulated in the International Military Tribunal Tokyo 1950 Principle VI are violated by the group. The impact of the designation of armed groups as terrorists by other countries in terms of international law is: Giving negative stigmatization and increasingly prolonged discrimination to the Hamas group as freedom fighters in the country where Hamas is located.